Career Aspirations, Preparedness, and Skill development: A study among the University Students in Bangladesh - Rifat, Ahsanul Haque; Sony, Sonya Farhana (Indonesian Journal of Education and Social Sciences, 2025)
Career development is crucial for university students to achieve their aspirations and imminent desired goals. Though have passionate determination, university students face the stark reality of lacking in necessary resources and proper facilities to nurture their skills and abilities compared to developed countries. This study aims to identify career aspirations and skill gaps, explore influencing factors, and identify skill development challenges among the students of Jatiya Kabi Kazi Nazrul Islam University, Mymensingh, Bangladesh. This study is conducted through a mixed-methods approach. For the quantitative data a total of 250 surveys (both offline and online) are collected, and for the qualitative data case studies (05) are used to collect data from the students by convenient sampling technique. The study findings revealed a strong preference (39%) for public service careers in government or civil service sectors. Parental influence (36%) and self-motivation (25%) were major factors, outweighing external figures like teachers (10%). Expected career challenges were uncertainty (20%), skills gaps (24%), and lack of experience (16%). Major skill development obstacles were lack of mentoring (20%), resources (19%), and practical experience (18%). Besides, the findings of this study will provide pivotal insights into enhancing career services and skill development programs in Bangladeshi universities to better prepare students for success in the professional world. The significance of the study is hidden in its latent efficiency to inform policymakers, educators, and others about the factors, and challenges that influence university students' career aspirations and preparedness.